2011
DOI: 10.1123/tsp.25.4.465
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Choking Under Pressure in Elite Golf: An Action Research Study

Abstract: The study examined the effect of an evidence-based intervention on choking in golf. It is informed by the work of Hill, Hanton, Matthews and Fleming (2010a) that explored the experiences of elite golfers who either choked or excelled under pressure. The perceptions of elite golf coaches who worked with both 'chokers' and those who excelled, were also considered. It revealed that choking may be alleviated through the use of process goals, cognitive restructuring, imagery, simulated training and a pre/postshot r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 61 publications
1
45
0
Order By: Relevance
“…Similar to Hill and Shaw's (2013) findings from five team sports (including rugby) the All Blacks coaches encouraged their players to adopt a process of positive reflection that used the choking experience constructively (also see Gucciardi et al, 2010). Furthermore, Hill et al (2011) concluded that reflecting positively on negative events by drawing constructive lessons can encourage progression through experience by developing facilitative anxiety perceptions that prevent the lowering of confidence that can occur if the athlete is allowed to mull over (ruminate) negative experiences such as the stereotype threat of being 'RWC chokers'. Beilock and McConnell (2004) concluded that "awareness of a negative stereotype about one's social group hurts performance" (p. 598), consequently efforts to engage in positive reflection and reappraisal of stereotype threats such as those employed by the All Blacks' coaches appeared to be a particularly proactive method for reducing the effect of such threats.…”
Section: Learning From the 2007 Rugby World Cup (Rwc)mentioning
confidence: 69%
See 2 more Smart Citations
“…Similar to Hill and Shaw's (2013) findings from five team sports (including rugby) the All Blacks coaches encouraged their players to adopt a process of positive reflection that used the choking experience constructively (also see Gucciardi et al, 2010). Furthermore, Hill et al (2011) concluded that reflecting positively on negative events by drawing constructive lessons can encourage progression through experience by developing facilitative anxiety perceptions that prevent the lowering of confidence that can occur if the athlete is allowed to mull over (ruminate) negative experiences such as the stereotype threat of being 'RWC chokers'. Beilock and McConnell (2004) concluded that "awareness of a negative stereotype about one's social group hurts performance" (p. 598), consequently efforts to engage in positive reflection and reappraisal of stereotype threats such as those employed by the All Blacks' coaches appeared to be a particularly proactive method for reducing the effect of such threats.…”
Section: Learning From the 2007 Rugby World Cup (Rwc)mentioning
confidence: 69%
“…I'd rather go through life being under pressure, than just cruising" (Chalmers, 2008). Similar to the cognitive restructuring identified by Hill et al (2011), the All Blacks viewed pressure as being positive, not negative; as being helpful, not a hindrance; as something to be savored, not feared; pressure becomes your friend, not your enemy; pressure becomes an opportunity, not an obstacle (All Blacks choking, 2011, Sept 5th; Hansen, 2011;Howitt & Henry, 2012;McCaw & McGee, 2012;Paul, 2012b, Oct 23rd;Stanley, 2012). As the following quote from Graham Henry (All Blacks head coach) indicates, the All Blacks adopted the attitude that the public expectation was a sign of respect: "[The public expectation is] inspirational.…”
Section: Public Expectation and Pressurementioning
confidence: 81%
See 1 more Smart Citation
“…However, most of the studies presented in articles are in the area of sports psychology or motor learning, and seem to relate primarily to the physicality of the body as something which the golfers have to learn to handle and cope with in a controlled manner when optimising their performance (Smith et al 2000, Nicholls 2007a, Wulf and Su 2007, Bell and Hardy 2009, Gucciardi et al 2010, Nicholls et al 2010, Hill et al 2011. Only a minority of studies revolve specifically around how golfers sense or feel the physicality of their bodies when training and performing their complex skills.…”
mentioning
confidence: 94%
“…a psycho-neuromuscular impediment, might affect the execution of the putting stroke in golf (Smith et al 2000). Along the same lines, and in the case of an acute performance breakdown, when a golfer 'overthinks' and this gets in the way of executing a practised routine, the concept of 'choking' has been investigated to see how this might be used constructively for improving performance (Gucciardi et al 2010, Hill et al 2011. These studies of how golfers might use their skills successfully in performance implicitly draw on the subject's experience of her body as related to two dimensions of subject's self-consciousness -the consciousness taking control of the unconscious.…”
mentioning
confidence: 99%